Analisis peranan e-commerce terhadap perkembangan Usaha Mikro Kecil dan Menengah - Nisa’, Mashlahun (Maliki Interdisciplinary Journal, 2023)
Todays technological developments are increasingly advanced with the existence of social media and electronic devices that can help the development of UMKM become easier. If you can make good and maximum use of E-commerce. The method used in this research is descriptive quantitative. E-commerce plays an important role in the development of UMKM, including in terms of product marketing. Promotional activities can be done easily which can make energy and time effective. With the proper and maximum use of E-commerce, it will be able to develop UMKM.